Representasi Profesionalisme Jurnalis Dalam Film The Journalist (Analisis Sepuluh Elemen Jurnalisme) - Nasya Ilmalia; Candra Darmawan (Program Studi Jurnalistik, Universitas Islam Negeri Raden Fatah Palembang, 2023)
Journalism has many interesting sides to be made into a film. There are many films and dramas that raise the theme of journalism, one of which is the film The Journalist. The Journalist, which was first released in Japan on 28 June 2019, was directed by Michihito Fujii. The film, adapted from a novel of the same name, tells the story of a young journalist named Erika Yoshioka who is asked to investigate a case about a new university construction plan that has many irregularities in it. This research is entitled